Systematic Pelvic and Para-Aortic Lymphadenectomy During Fertility-Sparing Surgery in Patients With Early-Stage Epithelial Ovarian Cancer: A Retrospective Study - Li, Tingting; Liu, Ya; Xie, Sixia; Wang, Hongjing (Frontiers in Oncology, 2022)
Objective. The implication of pelvic and para-aortic lymphadenectomy in surgical staging of early-stage epithelial ovarian cancer (eEOC) is still debated. Limited data are available about systematic lymphadenectomy during fertility-sparing surgery (FSS) in patients with eEOC. Methods. The medical records of 38 patients with FIGO stage I EOC and below 40 years who underwent FSS at our hospital between January 2003 and December 2018 were retrospectively reviewed. Results. Among them, 18 patients (47.4%) underwent comprehensive lymphadenectomy, 11 patients (28.9%) underwent lymph node sampling, and 9 patients (23.7%) did not undergo lymphadenectomy. There was no statically significant difference in age, histology, grade, surgical approach, chemotherapy, and gestation among the three groups. With a median follow-up of 52.5 months (range: 24–153), three patients (7.9%) with FIGO stage IC EOC developed tumor recurrence. In these patients, progress-free survival(PFS) was 92.1%, and overall survival (OS) was 94.7%. No significant difference in the OS. Three patients had Among all the patients, 15 patients (39.5%) had gestation after treatment, and 23 patients (60.5%) did not have gestation after treatment. Conclusion. The number of lymph nodes removed did not significantly affect survival eEOC with FSS. Systematic pelvic and para-aortic lymphadenectomy could not be performed for mucious eEOC patients with FSS if intraoperative freezing in confirmed and no suspicious lymph nodes are found. A better understanding of sentinel lymph node biopsy may help to identify whether the patient requires FSS.